In-situ polymerization of styrene in AAO nanocavities - Giussi, Juan Martín (2013)
One of the most promising aspects of the alumina oxide (AAO) template is the ability to generate a variety of different hierarchical one-dimensional (1D) polymer morphologies with structural definition on the nanometric scale. In-situ polymerization of monomers in reduced spaces of porous aluminum oxide (AAO) nanocavities can give rise to the direct production of versatile polymer nanostructures. In this work, porous anodic aluminum oxide (AAO) devices of 35 nm of diameter have been obtained by a two-step electrochemical anodization process and used as a nanoreactor to study the radical polymerization kinetics of styrene (St) in confinement and the results compared to those of polymerization in bulk. SEM morphological study has been conducted to establish the final structure of obtained polymer nanostructures. Confocal Raman microscopy has been performed to study the formation of the polymer through the AAO cavities as a function of time and with this methodology it has been possible to establish the monomer conversion for styrenic polymerization in AAO devices. Polystyrene obtained in the nanoreactor was characterized by SEC, NMR, TGA and DSC and the properties compared with those of bulk polymer. It was found that both the average molecular weights and polydispersity index of nanostructured polymer are lower than those obtained for bulk polymer. NMR studies have shown that the use of a reactor with nanometric size dimensions gave the obtained polystyrene greater stereospecificity than that obtained in bulk. Thermal stability and Tg values are higher for nanostructured than bulk polymers. Moreover, the methodology proposed in this work, using AAO nanocavities as nanoreactors for polymerization reaction, can be generalized and applied to obtain polymer nanostructures of very different chemical nature and morphology by choosing the appropriate monomer or monomer reactants and by tailoring the dimension of AAO cylindrical nanocavities, that is, diameter from 20 to 400 nm and length from a few to hundreds of microns.